ESBL-producing Escherichia coli and Klebsiella pneumoniae in two major Lebanese hospitals: molecular epidemiology and correlation with consumption - Anas Obeid; Peter Maliha; Samah Abdallah; Estelle Akl; Maria Deeb; Hassan El Moussawi; Elie Salem-Sokhn; Ghassan Matar; Ziad Daoud (Journal of Infection in Developing Countries)
Introduction: Extended-spectrum – beta lactamases (ESBLs) are increasingly detected globally among Escherichia coli and Klebsiella pneumoniae. The correlation between antibiotics use and resistance, though not fully described, has been addressed and shown in several studies. In this study, the profiles of ESBLs in E. coli and K. pneumoniae isolated from two Lebanese hospitals and their relationship to antibiotic consumption were determined.